Heart rate profile and variability in cross country cycling athletes - Ribeiro, E.; Ribeiro, C. A. F.; Tavares, P. (International Journal of Sports Science, 2016)
Cross-country cycling is a very demanding sport. The characteristics of the competition are mainly aerobic but in a maximal effort. Due to the heart rat achieved during competition we may expect that there is some cardiovascular risk involved. Thus, the main aim of this work was to study the autonomic nervous system balance and heart rate recovering in cross-country cycling athletes. The autonomic nervous system was evaluated by measuring the heart rate variability. Our results suggested that in those athletes there is a very good balance between sympathetic and parasympathetic systems as well as a very efficient heart rate recovery. So, there is no indication of cardiovascular risk, increase in mortality or sudden death.